2004
DOI: 10.1002/ejic.200400404
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses, Structures and Reactivity of Electron‐Rich Fe and Ru Complexes with the New Pentadentate Ligand Et2NpyS4−H2 {4‐(Diethylamino)2,6‐bis[(2‐mercaptophenyl)thiomethyl]pyridine}

Abstract: The new pentadentate thioether thiolate ligand Et2NpyS42− {= 4‐(diethylamino)‐2,6‐bis[(2‐mercaptophenyl)thiomethyl]pyridine(2−)} has been synthesised from dimethyl 4‐bromopyridine‐2,6‐dicarboxylate by treatment with Et2NH followed by reduction and tosylation. The tosylated product was subsequently used for the template alkylation of [Ni(S2C6H4)2]2− to give [{Ni(Et2NpyS4)}2] (4). Acidic hydrolysis of 4 resulted in the formation of the ligand Et2NpyS4−H2·HCl (5). The dianion Et2NpyS42− reacted with FeCl2·H2O to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…Oxidation of sulfur and consequent exchange of the co-ligand N 2 H 4 by H 2 O is an interesting phenomenon in relation to hydrogen bonding. The exchange of N 2 H 4 by H 2 O may happen due to the fact that the N 2 H 4 co-ligand is stable only in the presence of hydrogen bonding as reported earlier [7]. Oxidation of the sulfur donors damages the hydrogen bonding and as a result the N 2 H 4 decoordinates to leave a free coordination site.…”
Section: Synthesis and Characterizationmentioning
confidence: 88%
See 3 more Smart Citations
“…Oxidation of sulfur and consequent exchange of the co-ligand N 2 H 4 by H 2 O is an interesting phenomenon in relation to hydrogen bonding. The exchange of N 2 H 4 by H 2 O may happen due to the fact that the N 2 H 4 co-ligand is stable only in the presence of hydrogen bonding as reported earlier [7]. Oxidation of the sulfur donors damages the hydrogen bonding and as a result the N 2 H 4 decoordinates to leave a free coordination site.…”
Section: Synthesis and Characterizationmentioning
confidence: 88%
“…Reactions with O 2 are distinct from reactions with H 2 O 2 in that the former can lead to products incorporating both atoms of O 2 (a four-electron, dioxygenase-like oxidation), whereas peroxide sequentially oxidizes sulfur by two electrons with the transfer of one oxygen. In a previous paper, we found that the iron thiolate can be converted to a S-bound sulfinato complex by the incorporation of dioxygen [7]. In this article we report an oxidation of a Ru(II) alkylthiolate hydrazine complex 3 upon reaction with H 2 O 2 that also leads to ligand oxidation.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…21 The Ru-S(1) bond length is 2.3856(9) Å and is close to previously reported Ru-S thiolate bonds. [43][44][45][46] The Ru-S thioether bond lengths in 2a for Ru-S2 and Ru-S3 are …”
mentioning
confidence: 99%